Religious Moderation In An Islamic Perspective: A Review of Islamic Education - Sulaiman, Baso; Yusuf, M. Suyuti (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study examines the role of religious moderation in shaping attitudes of tolerance, respecting differences, and creating harmony between religious communities. This research uses qualitative research methods by conducting library research and processing literature relevant to the research topic. Researchers were the main instruments in this study, and data collection was carried out using the triangulation method. Data is collected through literature such as books, magazines, articles, and readings relevant to the discussion. The data is then analyzed and compiled to form accurate conclusions. The results of this study show that religious moderation has an essential role in maintaining balance in carrying out religious teachings, avoiding extremism, and creating harmony between religious communities. The principles of religious moderation include tawassuth (neutrality), tawazun (balance), i'tidal (straight and firm), tasamuh (tolerant), musawah (egalitarian and non-discriminatory), aulawiyah (prioritizing), tahaddhur (civilization), and tathawwur wa ibtikar (dynamic, creative, and innovative). Implementing religious moderation is expected to create a harmonious, peaceful, and tolerant society, according to the spirit of Bhinneka Tunggal Ika.